Ответы и объяснения

Лучший Ответ!
  • armen98
  • почетный грамотей
2012-10-24T20:45:27+04:00

Задача упростится если ввести новую переменную \sqrt[4]{ab}

Тогда:\sqrt[4]{a^3b^3}=t^3; \sqrt{ab}=t^2

(\frac{t-t^2}{1-t^2}+\frac{1-t}{t})*\frac{1+t^3}{t}-\frac{1-t-t^2}{t^2}=\frac{t^2(1-t)+(1-t^2)(1-t)}{t(1-t^2)}*\frac{1+t^3}{t}-\frac{1-t-t^2}{t^2}=

=\frac{t^2+1-t^2}{t(1+t)}*\frac{(1+t)(1-t+t^2)}{t}-\frac{1-t-t^2}{t^2}=\frac{1-t+t^2}{t^2}-\frac{1-t-t^2}{t^2}=

=\frac{1-t+t^2-1+t+t^2}{t^2}=\frac{2t^2}{t^2}=2